Telemonitoring and Telerehabilitation Can Improve Health Status for Heart Failure? A Review - Firdaus, Eza Kemal; Wijayanti, Indri; Purwatiningsih, Purwatiningsih (Journal of Advanced Health Informatics Research, 2023)
This review aims to enhance the health status of patients with heart failure. This review will look into the possibilities of telemonitoring and Telerehabilitation as a nursing care delivery paradigm. “Reviews of the literature focus on problems, approaches, formulas, and suggestions for additional research. PUBMED, SAGE Journal, Wiley Online Library, Proquest, and ScienceDirect were all used to conduct extensive research on the subject. Among the telemonitoring and Telerehabilitation methods found in treating heart failure patients were websites, phone calls, and applications.” Telemonitoring and Telerehabilitation can decrease rehospitalization and mortality in heart failure patients while enhancing health status, self-care, self-efficacy, clinical management, and education